Clinical Evaluation of a Fissure Sealant Placed by Acid Etching or Er: YAG Laser Combined with Acid Etching - DURMUŞ, BAŞAK; KARGÜL, BETÜL; EREN GİRAY, FİGEN; PEKER, MEHMET SERTAÇ (QUINTESSENCE PUBLISHING CO INC, 2017)
Purpose: To evaluate the efficacy of conventional acid etching alone (acid etching) and Er:YAG laser combined with acid etching (laser + acid etching) on fissure sealant (FS) retention of first permanent molars (FPMs) after 18 months. Materials and Methods: Using a split-mouth design in 51 children, a total of 204 FPMs were sealed with acid etching alone or laser plus acid etching (laser+acid). The retention of sealants and occurrence of caries were evaluated at 3, 6, 12, and 18 months. Statistical analysis was performed using Pearson's chi-squared tests. Results: The retention rate for FS in the laser+acid group was significantly higher than that of the acid-etch group at 12 (p = 0.0161) and 18 (p = 0.0227) months. Six FSs in the acid group and five FSs in the laser+acid group were completely lost after 18 months. The incidence of caries in the acid-etch group was 22% (n = 18) vs 10% (n = 8) in the laser+acid group at 18 months. The difference in caries development between the groups was not significant (p > 0.05). Conclusions: As enamel pretreatment, Er: YAG laser combined with acid etching significantly improves FS retention over conventional acid etching alone.
Keywords: dental acid etching; lasers; pit and fissure sealants; PRIMARY TEETH; IN-VITRO; AIR-ABRASION; SPLIT-MOUTH; ENAMEL; PRETREATMENT; PIT; RETENTION; MICROLEAKAGE; IRRADIATION